In accordance with IAS 11, «Construction Contracts» recognition of revenue and costs, disclosure of information (Journal of Economic Research & Business Administration, 2016)
In accordance with International Accounting Standard (IAS) 11, «Con struction contracts» reflects the establishment of the accounting treatment for revenue and costs associated with construction contracts. Due to the nature of the activity, undertaken in construction contracts, the date of commencement of contract activity and the date of its completion usu ally fall into different reporting periods. Thus, the basis of accounting for construction contracts is the allocation of revenue and costs of a construc tion contract to accounting periods, in which construction works are per formed. The methods are disclosed, used to determine revenue and costs of contract, recognised in the accounting period; and the methods, used to determine the stage of completion of the incomplete contracts.
Keywords: construction contracts; a fixed price contract; a «cost-plus» contract; incentive payments.